Development of safety health monitoring device to prevent and control risk in confined space - Saeed, Hussein Ali (2019)
IoT (the Internet of Things) has become an interesting topic in the field of technology research. It is basically connected to each other through the Internet from the device. We usually think of IoT in terms of independent cars and smart homes, but some of the best applications of Internet technology stuff in a very practical area. The main contribution of this thesis is to introduce an approach and provide a supporting platform for the automated synthesis of interoperability software artifacts. Such artifacts enable the interconnection between mobile Things that employ heterogeneous middleware protocols. Our platform further supports evaluating the effectiveness of the interconnection in terms of end-to-end QoS. More specifically, we derive formal conditions for successful interactions, and we enable performance modeling and analysis as well as end-to-end system tuning, while considering several system parameters related to the mobile IoT.